Sistem Pemeliharaan Ternak Babi Di Desa Golo Kabupaten Halmahera Barat - Meidogda, Meki; Saelan, Emy; Lestari, Sry; Syafie, Yunus (Universitas Negeri Gorontalo, 2025)
The study of pig husbandry system in Golo Village, West Halmahera Regency was conducted with the aim of determining the pig husbandry system carried out by pig farmers in Golo Village with 30 respondents. The method used in this study was quantitative analysis with a descriptive statistical approach. The parameters observed in this study include: General description of pig farming in Golo Village, Sahu District, Pig Growth in Golo Village, Sahu District, Pig Husbandry System in Golo Village, Sahu District, and penning system. The results of this study indicate that the pig husbandry system in Golo Village, West Halmahera Regency, is 10% in pens, 73.33% in pens at night and released during the day and 16.67% are not in pens.